Cooling performance test and analysis of a radiant–convective air-conditioning terminal device with parallel pipes. (3rd April 2017) - Haiwen, Shu; Tingyu, Wang; Jing, Shi; Hongbin, Wang; Lin, Duanmu; Mingrui, Zhu
Abstract : A new type of air-conditioning terminal device that could be used both for cooling in summer and heating in winter was studied in the research. In order to obtain the heat transfer characteristics of the device, a test rig was set up and measured, and then the cooling capacity and the percentage of radiation heat exchange of the device were calculated and analyzed. The results show that the total cooling capacity of the device can reach 631.0 W (i.e., 143.8 W/m 2 ) under the supply water temperature of 8°C and the water flow rate of 240 L/h. The proportion of the radiation heat exchange rate to the total heat exchange rate is around one-third. The cooling capacity comparison between the device and the radiant cooling ceiling shows that the cooling capacity of the device increases by about 57.6% per square meter surface area over the value of the radiant cooling ceilings at the same inlet cooling medium temperature. In the end, the differences between this radiant–convective air-conditioning terminal device and other common space heating/cooling terminal devices were summerized.